2010
DOI: 10.2320/matertrans.m2010244
|View full text |Cite
|
Sign up to set email alerts
|

<I>Ab Initio</I> Molecular Dynamics Study of Fe Adsorption on TiN (001) Surface

Abstract: The adsorption energy of atomic Fe on TiN (001) surface was examined by first-principles calculations. The inter-atomic interaction mechanism between TiN crystal and Fe atom was investigated using ab initio molecular dynamics simulation. It was found that the N site is more preferable than Ti and bridge sites for Fe atom. These results may be of importance for further understanding heterogeneous nucleation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, ab initio molecular dynamics (AIMD) allows for quantum mechanical-based calculations to be performed at non-zero temperatures. AIMD has been utilized to study a variety of systems including liquid phase diffusion in Al-Si (Manga and Poirier, 2018), the adsorption energy of Fe on TiN surfaces (Wang et al, 2010), NaCl dissolution in water (Timko et al, 2010) and finite temperature phonon dispersion curves in bcc Zr and bcc (Li Hellman et al, 2011). Hood et al (2008) have previously utilized AIMD to study the equation of state of U and the variation in density of states for the liquid phase of U at two unique temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…However, ab initio molecular dynamics (AIMD) allows for quantum mechanical-based calculations to be performed at non-zero temperatures. AIMD has been utilized to study a variety of systems including liquid phase diffusion in Al-Si (Manga and Poirier, 2018), the adsorption energy of Fe on TiN surfaces (Wang et al, 2010), NaCl dissolution in water (Timko et al, 2010) and finite temperature phonon dispersion curves in bcc Zr and bcc (Li Hellman et al, 2011). Hood et al (2008) have previously utilized AIMD to study the equation of state of U and the variation in density of states for the liquid phase of U at two unique temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…First, we testify that the Fe atom prefers to be in the C-top position, but not above the M atom or bridge site, as was also obtained in [22] for Fe on (0 0 1)TiN. Table 1.…”
Section: Fe Adsorption On the (0 0 1)mx Surfacementioning
confidence: 91%
“…Ab initio calculations of the Fe adsorption on the (0 0 1)TiN surface were performed to understand the nucleation mechanism of Fe on the TiN particles [22]. These calculations demonstrated that adsorption energy is a reliable parameter to describe a first stage of nucleation and the knowledge of adsorption properties of carbides and nitrides is important to predict the efficient precipitates in steel.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption energy on the WO 3 surface varied in a range of −1.25-0.97 eV/atom, depending on the types of adsorbates (NO, CO, or H 2 O) [71][72][73][74][75], while those of NO and CO 2 on the TiO 2 surface were in a narrow range of 0.03-0.74 eV/atom [76][77][78]. As for the nitride surfaces, the adsorption sites obviously impact the adsorption energies [79][80][81]. The interaction between oxygen/H 2 O molecules and the metal atoms in the nitrides was considerably stronger, resulting in a lower adsorption energy [80,81].…”
Section: Frictionmentioning
confidence: 99%